Faktor - Faktor Yang Mempengaruhi Peran Dinas Perindustrian Dan Tenaga Kerja Dalam Meningkatkan Kapasitas IKM “Kelompok Tani Mutiara” Nagari Labuah Gunuang Kabupaten Lima Puluh Kota - Vinta Lestari; Fitri Eriyanti (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study was conducted to identify the factors affecting the Department of Industry and Manpower in enhancing the capacity of SMEs within the Mutiara Farmer Group in Nagari Labuah Gunuang, Lareh Sago Halaban District, Lima Puluh Kota Regency. The study employs qualitative research with a descriptive method. Data validity in this research is tested using source and method triangulation techniques. The findings indicate that the main hindering factors include, lack of human resources, and low participation of SME members as well as limited cooperation with palm sugar farmers, while the main supporting factor is the adequate production facilities.